REPRESENTASI SOSIAL TENTANG PEMIMPIN ANTARA DUA KELOMPOK USIA DAN SITUASI SOSIAL YANG BERBEDA DI JAKARTA DAN PALEMBANG, INDONESIA - Putera, Idhamsyah Eka; Wardhani, Citra; Muwardani, Resky (Faculty of Psychology, Diponegoro University, 2009)
The study focuses on the concept of leader among two different age groups in two cities in Indonesia. There are local situations that make the two cities have different leadership salience. Jakarta had low leadership salience with no local election apparent while Palembang had a high leadership salience due to the upcoming local election when the research took place. For the last ten years, democracy has been widely recognized in Indonesia. This new concept is believed to create different concept of leaders among people with different age groups and with different leadership saliences. The research was to test if different concepts of leader exist among different age groups. The study used word association technique to collect data from a total of 463 participants in Jakarta and Palembang. Participants were classified into two different age groups, younger age group (17-40 years old), and older age group (40-65 years old). The study show that there are same and different representations of leader between two age groups in Jakarta, while participants in Palembang shows similar representations between the two age groups. Most participants relate the meaning of leader with personal traits. There is a different representation in Jakarta and Palembang due to the social contexts exist when the study took place. The democracy process implemented in Indonesia during the last decade show its effect on the representations of leader in younger age group in Jakarta. Discussion is provided.